The Family as a Servant of State (Hekima Review, 2016)
At the end of his creating work, God made mankind male and female in his likeness. He “blessed them and said to them: Be fertile and multiply, fill the earth and subdue it (Gen. 1:28).” Through this blessing, God sanctified the first human family and signed a covenant with humanity. From this covenant, the Family becomes the “bonum prolis, bonum fidei and bonum sacramenti grounded in Christian love existing between Christ and the Church.” Since every human being, as a member of the larger community called State, receives his or her life and is brought up and educated first in his or her family, we consider the Family as the foundation for a State. The family renders a noble service to the State by offering citizens. In this sense, we may say: “Familia stati ancilla.”